ANALISIS SWOT PERJANJIAN PERDAGANGAN INDONESIA – CHILE CEPA - Faliq Hukma Al Nafi; Marsanto Adi Nurcahyo (BBM (Buletin Bisnis & Manajemen), 2021)
Indonesia Chile-CEPA agreement has been entry-into-force since August 2019. Trade between Indonesiaand Chile has alternated surpluses and deficits during the 2015-2020 periods. This study will analyzehow the internal and external factors of the trade cooperation between Indonesia and Chile are. Thispaper reveals strategies that Indonesia can use in trade based on a SWOT analysis. This research waswritten using descriptive method with qualitative approach. Data collection techniques were carried outby interview. The results of the interview are used as a SWOT matrix. The results of this study indicatethat Indonesia's internal and external conditions support the cooperation with Chile. The internalfactors on this research are the condition of economy, trade commodities, size of the Indonesianpopulation, scope of the agreement, and level of trade between Indonesia and Chile. The externalfactors based on this research are the potential for tariff reduction in trade, expansion of Indonesianmarket in South America through Chile, opening of investment and trade opportunities, economic andpolitical conditions in South America, and geographic conditions of Indonesia and Chile. The results ofthe SWOT analysis show that Indonesia can use various strategies in trade with Chile.